2012
DOI: 10.1556/eujmi.2.2012.3.10
|View full text |Cite
|
Sign up to set email alerts
|

Murine adult neural progenitor cells alter their proliferative behavior and gene expression after the activation of toll-like-receptor 3

Abstract: Viral infections during pregnancy significantly increase the risk for psychological pathologies like schizophrenia in the offspring. One of the main morphological hallmarks of schizophrenia is a reduced size of the hippocampus. Since new neurons are produced in this particular brain compartment throughout life, it might be possible that low neurogenesis levels triggered by a maternal viral infection contribute to developmental deficits of the hippocampus. We injected polyinosinic:polycytidylic acid (Poly I:C) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…A reduction in the number of reelin-positive cells was observed in the same animals, however, suggesting a potential defect in cell migration and morphogenesis of the DG (Depino, 2015). In vitro assays using DG neural progenitor cells treated with Poly(I:C) showed that direct TLR3 activation in these cells could increase proliferation; however, a decrease in the number of cells immunoreactive for the proliferation marker Ki67 was observed in the DG of adult MIA animals (Melnik et al, 2012). Further in vitro evidence suggests that IL-1ß signaling may contribute to the decrease in proliferation of neural progenitor cells isolated from ventral mesencephalon (Crampton et al, 2012).…”
Section: Effect Of Mia On Neurogenesis and Neuronal Developmentmentioning
confidence: 89%
See 1 more Smart Citation
“…A reduction in the number of reelin-positive cells was observed in the same animals, however, suggesting a potential defect in cell migration and morphogenesis of the DG (Depino, 2015). In vitro assays using DG neural progenitor cells treated with Poly(I:C) showed that direct TLR3 activation in these cells could increase proliferation; however, a decrease in the number of cells immunoreactive for the proliferation marker Ki67 was observed in the DG of adult MIA animals (Melnik et al, 2012). Further in vitro evidence suggests that IL-1ß signaling may contribute to the decrease in proliferation of neural progenitor cells isolated from ventral mesencephalon (Crampton et al, 2012).…”
Section: Effect Of Mia On Neurogenesis and Neuronal Developmentmentioning
confidence: 89%
“…on GD18-19) caused a reduction of proliferative cells labeled with BrdU in the dentate gyrus (DG) during fetal development and in the early postnatal stage (P14) (Cui et al, 2009). In vitro assays using DG neural progenitor cells treated with Poly(I:C) showed that direct TLR3 activation in these cells could increase proliferation; however, a decrease in the number of cells immunoreactive for the proliferation marker Ki67 was observed in the DG of adult MIA animals (Melnik et al, 2012). However, treatment with LPS earlier in gestation (25 mg/kg on GD9) did not affect neurogenesis in the mouse DG (Depino, 2015).…”
Section: Effect Of Mia On Neurogenesis and Neuronal Developmentmentioning
confidence: 99%
“…37 Melnik et al reported that IRF3 might be critical in regulating the development of neuronal progenitor cells. 38 The analysis of protein-protein interaction networks showed that IRF3 interacts with other schizophrenia susceptibility genes, such as CREB1, AKT1 and ESR1. 39 Furthermore, several studies identified that AKT1 and CREB1 were associated with synaptic plasticity in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…The interferon regulatory factor 3 gene (IRF3), located on chromosome 19q13, plays a key role in the innate immune system through the response to viral infection 37 . Melnik et al reported that IRF3 might be critical in regulating the development of neuronal progenitor cells 38 . The analysis of protein–protein interaction networks showed that IRF3 interacts with other schizophrenia susceptibility genes, such as CREB1, AKT1 and ESR1 39 …”
Section: Discussionmentioning
confidence: 99%
“…IRF3 is a key regulator of the innate immune system and is a plausible SCZ risk gene [88]. Recent studies show that it may be important in regulating the development of neuronal progenitor cells [48], and physically interacts with other schizophrenia susceptibility genes, such as CREB1, AKT1 and ESR1 [88]. We performed additional in-depth study of a region containing rs1080500, which is highlighted as possible causal variant by MetaChrom.…”
Section: Metachrom Predictions Of Variant Effects Assist Interpretation Of Gwas Resultsmentioning
confidence: 99%